2001
DOI: 10.1073/pnas.181257698
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated regulatory gene evolution in an adaptive radiation

Abstract: The disparity between rates of morphological and molecular evolution remains a key paradox in evolutionary genetics. A proposed resolution to this paradox has been the conjecture that morphological evolution proceeds via diversification in regulatory loci, and that phenotypic evolution may correlate better with regulatory gene divergence. This conjecture can be tested by examining rates of regulatory gene evolution in species that display rapid morphological diversification within adaptive radiations. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 44 publications
7
110
1
Order By: Relevance
“…This is analogous to studies considering rates of coding sequence evolution of duplicate genes (e.g. Ohta, 1994;Lynch and Conery, 2000;Barrier et al, 2001;Conery and Lynch, 2001;Thornton and Long, 2002;Kondrashov, 2005;Kondrashov and Kondrashov, 2006). (iii) Gene expression data from microarray experiments was compiled and related to Drosophila duplicate gene divergence (c.f.…”
Section: Introductionmentioning
confidence: 57%
“…This is analogous to studies considering rates of coding sequence evolution of duplicate genes (e.g. Ohta, 1994;Lynch and Conery, 2000;Barrier et al, 2001;Conery and Lynch, 2001;Thornton and Long, 2002;Kondrashov, 2005;Kondrashov and Kondrashov, 2006). (iii) Gene expression data from microarray experiments was compiled and related to Drosophila duplicate gene divergence (c.f.…”
Section: Introductionmentioning
confidence: 57%
“…It is therefore possible for regulatory changes to be quite important, but to still be essentially structural in nature Wagner and Lynch 2008). For example, protein evolution of regulatory genes has been associated with species radiations (Barrier et al 2001;Lawton-Rauh et al 2003) and other major morphological changes (Galant and Carroll 2002;Ronshaugen et al 2002). In addition, positive selection shaping the pattern of substitution for various transcription factor families in plants and animals (Sutton and Wilkinson 1997;Fares et al 2003;Jia et al 2003Jia et al , 2004Martinez-Castilla and Alvarez-Buylla 2003;Balakirev and Ayala 2004;Moore et al 2005) may have direct phenotypic consequences.…”
Section: T He Integration Of Evolutionary and Developmentalmentioning
confidence: 99%
“…Also, it is noteworthy that the dN/dS rate ratio of dlx2 leading to the parrotfishes (0.33) is the highest of all six genes along this part of the phylogeny. An elevated level of variation in regulatory genes has often been shown to be associated with morphological diversity in plants (Aagard et al, 2006;Barrier et al, 2001). Recent exploration of skull function of labrid fishes in the context of a phylogeny has shown that the cheiline and scarine labrids are a hot-spot of structural and functional evolution in these fishes, and dlx2 is known to regulate formation of pharyngeal elements of the feeding apparatus during development (Qiu et al, 1997;Stock et al, 1996).…”
Section: Evolutionary Trends In Mitochondrial Nuclear and Nuclear Rmentioning
confidence: 99%
“…Many studies have used phylogenetic tools to generate evolutionary topologies of Hox genes and other regulatory loci (e.g., Kim et al, 2003;Purugganan, 1997;Santini and Bernardi, 2005;Wagner et al, 2005) yet there are few explorations of the phylogenetic utility of regulatory gene sequences in in larger, multi-locus phylogenetic analyses. Several recent examples in arthropods (Cook et al, 2001) and plants (Barrier et al, 2001;Fan et al, 2004) have shown that regulatory loci can make strong contributions to phylogenetic resolution. This work, particularly in plants, has shown that regulatory gene sequences and their protein products do not necessarily evolve more slowly than structural genes, and in fact may evolve significantly faster (Barrier et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation